A multi-grade reactive power utilization evaluation method for distribution networks with high renewables - Xu, Min; Yao, Wenqian; Zeng, Wanyan; Li, Tianting; Wang, Zhou; Dou, Qing (Frontiers in Energy Research, 2025)
This paper proposes a multi-grade reactive power utilization evaluation strategy for distribution networks with high renewables to identify the devices with low-grade utilization efficiency. Firstly, a suitability assessment indicator is presented to quantify the mismatch degree between reactive power demand and compensation capacity in distribution substations, and then a Kantorovich distance-based scenario reduction method is used to obtain typical reactive power load curves from historical data. Furthermore, influence factors on reactive power planning are investigated for distribution networks with different penetration level of renewable energy sources. Finally, considering zonal differences in load types and network structures, a multi-grade utilization evaluation strategy is proposed to identify inefficient reactive power equipment under various operating conditions. Comparative case studies have validated the superior performance of the proposed strategy for better utilization of reactive power compensation equipment.